2022
DOI: 10.3390/ani12131729
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glutamine Supplementation Alleviated Inflammation Responses and Improved Intestinal Mucosa Barrier of LPS-Challenged Broilers

Abstract: The present study was conducted to investigate the effects of glutamine (Gln) supplementation on intestinal inflammatory reaction and mucosa barrier of broilers administrated with lipopolysaccharide (LPS) stimuli. A total of 120 1-d-old male broilers were randomly divided into four treatments in a 2 × 2 experimental arrangement, containing immune challenge (injected with LPS in a dose of 0 or 500 μg/kg of body weight) and dietary treatments (supplemented with 1.22% alanine or 1% Gln). The results showed that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…The reasons are hypothesized as follows: (1) Alanyl‐glutamine dipeptide and/or VE might improve fish growth. Alanyl‐glutamine dipeptide (Yoon et al, 2020; Yu et al, 2016; Zhang et al, 2022) and VE (Noguchi, 2019; Zhou et al, 2013) were reported to improve fish growth. The same results were obtained in marine juvenile cobia ( Rachycentron canadum ) (Ding et al, 2017, 2018) and freshwater farmed tilapia (GIFT, Oreochromis niloticus ) (Ding et al, 2021; Xu, Zheng, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons are hypothesized as follows: (1) Alanyl‐glutamine dipeptide and/or VE might improve fish growth. Alanyl‐glutamine dipeptide (Yoon et al, 2020; Yu et al, 2016; Zhang et al, 2022) and VE (Noguchi, 2019; Zhou et al, 2013) were reported to improve fish growth. The same results were obtained in marine juvenile cobia ( Rachycentron canadum ) (Ding et al, 2017, 2018) and freshwater farmed tilapia (GIFT, Oreochromis niloticus ) (Ding et al, 2021; Xu, Zheng, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that when broilers were administered 2.5% DSS for 7 consecutive days from 15 to 21 days of age, the BW (573.83 g vs. 692.83 g) and ADG (20.43 g vs. 37.79 g) at 21 days of age were significantly lower than those belonging to the CT group [ 39 ]. Poor growth performance in broilers challenged with DSS may be attributed to several factors, including increased intestinal permeability caused by gut barrier dysfunction [ 40 ], lower nutrient absorption ability caused by reduced small intestinal apical hydrolase activities [ 41 ], liver inflammation and lipid metabolism disfunction [ 42 ], and immune stress that shifts dietary nutrients from growth processes to support various inflammatory immune responses and mediator syntheses [ 22 ]. Gut microbiota dysbiosis also inhibits growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…From 21 to 29 days of age, BW was continuously recorded to monitor body weight changes caused by DSS. Total BW and feed intake were recorded to calculate average daily gain (ADG), feed conversion ratio (FCR), and average daily feed intake (ADFI) according to the method proposed in a previous study [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Glutamine supplementation alleviates lipopolysaccharide-induced inflammatory responses by inactivating various signaling pathways, including TLR4/focal adhesion kinase/MyD88, TLR4/NF-κB, and TLR4/mitogen-activated protein kinases pathways. [73][74][75][76] In a double-blind, randomized, controlled pilot trial involving patients diagnosed with pelvic or abdominal malignancies undergoing abdominal radiotherapy, oral glutamine supplementation significantly reduced the expression of TLR-4 and NF-κB. [77] However, it's important to note that there have been conflicting findings in the literature.…”
Section: Inflammationmentioning
confidence: 99%